Mutual recovery in people with psychological disorders or functional diversity through the creative practice - Saavedra-Macías, F. Javier; Arias-Sánchez, Samuel; de la Cruz, Eylin; Galán, M. Luisa; Galván, Blanca; Murvartian, Lara; Vallecillo, Natividad (Arte, Individuo y Sociedad, 2016)
In this paper we introduce the concept of “mutual recovery” and we propose creative practices as efficient recovery tools people with both mental health problems as some sort of functional diversity. Compared with the traditional concept of “art therapy” we propose the concept of “creative practice” as more consistent with the model of “mutual recovery.” To do this, we first make a brief critical review of the relationship between art and madness. Next, we present the related concepts of “recovery” and “mutual recovery” in the context of what has become known as the “health humanities”. Finally, we describe two creative practices currently being tested in Spain in the context of the a international research project about mutual recovery:Creative workshops with people with serious mental illness at the Museum of Contemporary Art of Seville and the theater group of people with diverse functionality with the Down Syndrome Association of Seville.